(untitled) (Biuletyn Kryminologiczny, 2023)
Od 2022 roku Katedra Kryminalistyki Akademii Nauk Stosowanych im. Stanisława Staszica w Pile prowadzi cykl konferencyjny o międzynarodowym zasięgu pod nazwą: Criminology and Public Safety. Realizację tego przedsięwzięcia umożliwiło pozyskanie finansowania w ramach programu Doskonała Nauka - Wsparcie Konferencji Naukowych. W ramach cyklu obyły się dotąd dwie konferencje naukowe. W grudniu 2022 roku przeprowadzono konferencję pod nazwą: Interdisciplinary Perspectives on Crime, Criminal Justice and Public Safety. Natomiast konferencja zorganizowana roku 2023 nosiła nazwę: Criminology and Social Problems in Times of Change. Theory, Method and Practise. Z uwagi na międzynarodowy zasięg cyklu konferencyjnego jego językami są polski i angielski. Poruszana w ramach cyklu problematyka dotyczy generalnie czterech obszarów, którymi są: 1) wyniki najnowszych badań z zakresu kryminologii; 2) praca policyjna w aspekcie wyników najnowszych badań; 3) współczesne nurty w teorii i praktyce resocjalizacyjnej; 4) globalne, lokalne i glokalne konteksty bezpieczeństwa publicznego. Zyskało to akceptację szerokiego grona ekspertów reprezentujących zarówno środowiska akademickie, jak praktykę społeczną z terenu całej Polski a także USA, Wielkiej Brytanii, Niemiec, Czech, Norwegii i Ukrainy. Koncepcja cyklu konferencyjnego obejmuje też włączenie w prowadzony w jego ramach dyskurs młodzieży studenckiej. Stąd ważnym punktem corocznej agendy jest Międzyuczelniane Forum Studenckich Kół Naukowych. Since the year 2022, the Department of Criminology at the Stanisław Staszic Academy of Applied Sciences in Piła has been organizing an internationally acclaimed conference series titled: "Criminology and Public Safety". The implementation of this initiative was made possible through funding obtained as part of the Excellent Science - Support for Scientific Conferences program. Within the series, two scientific conferences have already taken place. In December 2022, a conference named: "Interdisciplinary Perspectives on Crime, Criminal Justice, and Public Safety" was conducted. Meanwhile, the conference organized in 2023 was titled: "Criminology and Social Problems in Times of Change: Theory, Method, and Practice". Due to the international scope of the conference series, its languages are Polish and English. The topics covered in the series generally revolve around four areas, which are: 1) the latest research results in criminology; 2) police work in the aspect of the latest research results; 3) contemporary trends in the theory and practice of rehabilitation; 4) global, local, and glocal contexts of public safety. The concept of the conference series has gained acceptance from a wide range of experts representing both academic environments and social practice from all over Poland, as well as the United States, the United Kingdom, Germany, the Czech Republic, Norway, and Ukraine. The concept of the conference series also includes the involvement of student discourse within it. Therefore, an essential point on the annual agenda is the Interuniversity Forum of Scientific Student Associations.